2014
DOI: 10.7863/ultra.33.11.1991
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Assessment of Spleen Size in Turkish Migrants With Familial Mediterranean Fever in Germany

Abstract: Objectives Familial Mediterranean fever (FMF) can be associated with splenomegaly. Prospective quantitative data are lacking. We performed a sonographic assessment of spleen size in patients with FMF and healthy control participants to assess its diagnostic value. Methods Patients with FMF according to the criteria of Livneh et al (Arthritis Rheum 1997; 40:1879–1885) who were in an asymptomatic interval and control participants were prospectively included in this study in Germany and underwent sonographic meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(60 reference statements)
0
2
0
1
Order By: Relevance
“…A recent study performed on Turkish migrants with FMF in Germany showed a larger splenic volume, in patients with FMF compared to healthy controls using sonography. 22 Due to clinical phenotype among some patients who are heterozygous for FMF, it can potentially be missed or stay undiagnosed. Further studies should highlight FMF as a potential cause of moderate splenomegaly in our Mediterranean population.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed on Turkish migrants with FMF in Germany showed a larger splenic volume, in patients with FMF compared to healthy controls using sonography. 22 Due to clinical phenotype among some patients who are heterozygous for FMF, it can potentially be missed or stay undiagnosed. Further studies should highlight FMF as a potential cause of moderate splenomegaly in our Mediterranean population.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid A accumulates mainly in the kidney, as well as the heart, spleen, thyroid and gastrointestinal tract. Mild splenomegaly is a finding in younger adults (83). In one half of the children with FMF splenomegaly is detectable by ultrasound (84).…”
Section: (V) Congestionmentioning
confidence: 99%
“…Некоторые авторы даже выделяют характерные черты, позволяющие дифференцировать ОАБ при ССЛ от острого аппендицита, при котором наблюдаются более высокие уровни микроальбуминурии и β2-микроглобулина в моче, а также прокальцитонина [13,27,28]. В диагностике ССЛ помогает УЗИ, при котором определяется значительное увеличение селезенки (>11 см), имеющее высокую специфичность для острой атаки ССЛ [13,29], как и лимфоаденит и перитонит в острый период. В исследовании S. Masatlioglu и соавт.…”
unclassified